Complex regional pain syndrome type I in a female division I soccer player: a level 4 case report - McAlear, G. E.; Popp, J. K. (International Journal of Athletic Therapy & Training, 2021)
An 18-year-old female, Division I soccer player was diagnosed with complex regional pain syndrome approximately 2 weeks after tarsal tunnel release surgery. Postsurgically, the patient reported a significant increase in neuropathic pain, swelling, paresthesia, skin temperature asymmetry, and allodynia of the plantar and dorsal aspects of the foot, which were initially attributed to other causes. The intense pain and delayed diagnosis led to a decline in mental health and suicide ideation. Once diagnosed with complex regional pain syndrome, an epidural was placed at L5/S1 with a continuous flow of lidocaine, resulting in functional restoration. The patient`s diagnosis and recovery were based on the collaborative efforts of the surgeon, sports medicine physician, pain management specialist, and athletic trainer. She returned to soccer participation with minimal symptoms. This case is unique because the symptoms of complex regional pain syndrome were attributed to other causes, resulting in a delayed diagnosis and appropriate treatment. This delay resulted in the patient threatening self-harm.